A Study of the Impact of Human Factors on Speeding Traffic Accidents - HOR, KHAI LUEN; Noorliyana Binti Omar, (Recent Trends in Civil Engineering and Built Environment, 2022)
Speeding is one of the major factors contributing in traffic accident and causes fatality and injury. However, the choice of driving speed always depending on the human factor. Thus, the main purpose of this study is to investigate the relationship between speeding and traffic accident. Besides, it also aims to determine the human factors which will lead a driver to speeding and collect the opinions from the respondents about the effective speed control actions. The data collected from 384 respondents via questionnaire were descriptive and inferential analyzed by using SPSS software. The findings of this study showed the relationship between speeding and the rate of traffic accident, the most probability human factor cause traffic accident. This study was also expected to has a contribution to the speed management in future study.